2016
DOI: 10.1016/j.jaci.2015.12.1326
|View full text |Cite
|
Sign up to set email alerts
|

Interfering with baffled B cells at the lupus tollway: Promises, successes, and failed expectations

Abstract: B cells play an important role in systemic lupus erythematosus by acting not only as precursors of autoantibody-producing cells but also as antigen-presenting, cytokine-secreting, and regulatory cells. Unopposed activation of B cells through their B-cell receptor for antigen, as seen in B cells lacking Lyn kinase, results in systemic autoimmunity. The B-cell activating factor of the TNF family (BAFF), nucleic acid-sensing Toll-like receptors (TLRs), and type I interferon can affect B-cell survival and decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 124 publications
0
6
0
Order By: Relevance
“…Various studies have shown that HCQ increases the intracellular pH and inhibits lysosomal activity in antigenpresenting cells (APCs), including plasmacytoid dendritic cells (pDCs) 35,36 and B cells 37 , and also blocks major histocompatibility complex (MHC) class II-mediated antigen presentation to CD4 + T cells, and thus prevents the differentiation of these T cells (such as T follicular helper cells) 38 . This also leads to a reduction in the production of cytokines, such as tumor necrosis factor-alpha (TNF-α), interleukin 6 (IL-6), granulocyte macrophage colony-stimulating factor (GM-CSF), and IL-1β 38,39 .…”
Section: Hcq Exerts Strong Immunomodulatory Effectsmentioning
confidence: 99%
“…Various studies have shown that HCQ increases the intracellular pH and inhibits lysosomal activity in antigenpresenting cells (APCs), including plasmacytoid dendritic cells (pDCs) 35,36 and B cells 37 , and also blocks major histocompatibility complex (MHC) class II-mediated antigen presentation to CD4 + T cells, and thus prevents the differentiation of these T cells (such as T follicular helper cells) 38 . This also leads to a reduction in the production of cytokines, such as tumor necrosis factor-alpha (TNF-α), interleukin 6 (IL-6), granulocyte macrophage colony-stimulating factor (GM-CSF), and IL-1β 38,39 .…”
Section: Hcq Exerts Strong Immunomodulatory Effectsmentioning
confidence: 99%
“…Type I IFNs increase B-cell survival factors production, such as BAFF (17). A feedback loop between BAFF and Type I IFNs has been proposed (18). Therefore, altering Type I IFN pathways can abrogate autoimmune phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, most of the biologics are designed to inhibit either proinflammatory cytokines or affect the regulation of Th1/Th17 pathways. Although the human monoclonal BAFF antibody belimumab was approved for systemic lupus erythematosus, having a low incidence of organ damage and an excellent safety profile [8], other BAFF inhibitors were much less beneficial in clinical trials, suggesting redundancies in B cell signalling/survival pathways, which should be better understood before future clinical trials are conducted [9]. Recently, blisibimod, a potent and selective BAFF inhibitor with a unique tetravalent, ''peptibody'' structure, has been introduced in clinical evaluation for the treatment of systemic lupus erythematosus (SLE) [10].…”
mentioning
confidence: 99%